2018
DOI: 10.18203/2394-6040.ijcmph20183610
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of undernutrition and its determinants among preschool children in a rural community of Shimoga, Karnataka

Abstract: Background: Undernutrition is a major health and nutrition problem in India especially among preschool children. It is an important cause of childhood mortality and morbidity and also leads to permanent impairment of physical and mental growth of those who survive. The objective of the study was to estimate the prevalence of undernutrition among preschool children in the study setting and to determine various factors associated with undernutrition of the child.Methods: A cross sectional study was conducted amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…This suggests that marginalized section of society, irrespective of religion is more affected. Similarly, Mane et al, (2018) could not find any association between the prevalence of wasting and stunting with religion of children, this finding is similar with our results.…”
Section: Factors Influencing Nutritional Status Of Children Socio-dem...supporting
confidence: 90%
See 2 more Smart Citations
“…This suggests that marginalized section of society, irrespective of religion is more affected. Similarly, Mane et al, (2018) could not find any association between the prevalence of wasting and stunting with religion of children, this finding is similar with our results.…”
Section: Factors Influencing Nutritional Status Of Children Socio-dem...supporting
confidence: 90%
“…This distribution is also not statistically significant. Similarly, Mane et al, (2018) in their study among under five in Shivamoga, Karnataka found that prevalence of stunting was directly proportional to birth order of children and this association is statistically significant (p=0.023).…”
Section: Factors Influencing Nutritional Status Of Children Socio-dem...mentioning
confidence: 79%
See 1 more Smart Citation
“…After having a perusal of the previous studies, it is found that there is an anomaly in the age group selection for pre-school children in the studies of Indian settings as well as studies conducted in foreign countries (28,(32)(33)(34)(35)(36)(37)(38)(39). The age group ranges from 0-7 years in these studies.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Leaving aside the debate of age groups of pre-school children, this study surveyed the previous studies which investigated the risk factors of stunting among younger children. It has been found that individual child characteristics, e.g., child's age, sex, birth interval, birth order and birth weight are the associated factors of stunting (32,34,36,37,43,44). Many studies found that children born with low birth weight are more prone to become stunted in their childhood (45)(46)(47)(48)(49)(50)(51).…”
Section: Review Of the Literaturementioning
confidence: 99%